The actual use and status of honorifics in the perception of young Japanese native speakers - Duc-Harada, Patrycja (Silva Iaponicarum, 2025)
This paper analyses honorifics use among young Japanese native speakers with reference to their attitude and knowledge towards its current state. The outcomes of the analysis reference two pragmatic changes that are recently observed within this category: simplification and equalization. The paper is divided into two parts: theoretical and analytic. In the theoretical part such honorific oppositions as: “vertical/ horizontal”, “standard/non-standard”, “public/private” will be discussed with examples. The analytic part contains the analysis of the survey research supported with a post-survey discussion conducted in 2022–2023 at Japanese universities with 276 respondents. The aim of the analysis is to verify the impact of factors including: age, gender, status, relation with the listener, and sphere of communication on the use of honorific markers. It also evaluates young people’s awareness of vertical/horizontal honorifics and their significance, and discusses their attitude towards the relevant changes. The conclusion suggests that it is conflict avoidance and the concern for good relationships with receivers that determines young people’s language choice.